2003
DOI: 10.4049/jimmunol.170.6.3195
|View full text |Cite
|
Sign up to set email alerts
|

The Dendritic Cell-Specific Chemokine, Dendritic Cell-Derived CC Chemokine 1, Enhances Protective Cell-Mediated Immunity to Murine Malaria

Abstract: Cell-mediated immunity plays a crucial role in the control of many infectious diseases, necessitating the need for adjuvants that can augment cellular immune responses elicited by vaccines. It is well established that protection against one such disease, malaria, requires strong CD8+ T cell responses targeted against the liver stages of the causative agent, Plasmodium spp. In this report we show that the dendritic cell-specific chemokine, dendritic cell-derived CC chemokine 1 (DC-CK1), which is produced in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 58 publications
2
15
0
1
Order By: Relevance
“…Furthermore, CCL18 is chemotactic for T cells (30) suggesting that this chemokine plays a role in the organization of T cell responses. This idea is supported by a recent study demonstrating that human CCL18 enhanced Ag-specific primary CD8 ϩ T cell responses when coadministered with malaria vaccines in mice (31). In this study, we report that CCL18 was absent in the normal skin of healthy individuals and in the nonlesional skin of atopic individuals but showed abundant expression in lesional atopic dermatitis.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, CCL18 is chemotactic for T cells (30) suggesting that this chemokine plays a role in the organization of T cell responses. This idea is supported by a recent study demonstrating that human CCL18 enhanced Ag-specific primary CD8 ϩ T cell responses when coadministered with malaria vaccines in mice (31). In this study, we report that CCL18 was absent in the normal skin of healthy individuals and in the nonlesional skin of atopic individuals but showed abundant expression in lesional atopic dermatitis.…”
Section: Discussionsupporting
confidence: 77%
“…The alternative macrophage activation-associated chemokine PARC/CCL18 is mainly produced by antigen-presenting cells induced by Th2 type cytokines and may exhibit dual functions, with pro-and anti-infl ammatory properties [43]. PARC/ CCL18 was found to enhance protective cell-mediated immunity in murine malaria suggesting this chemokine as a potential adjuvant to enhance adaptive immune responses against Plasmodium yoelii infection [44]. In our study, plasma levels of TARC/CCL17 and PARC/CCL18 were similarly high in children with severe malaria and in adults with uncomplicated malaria, suggesting that even though being diminished in children to adult levels, PARC and TARC may not be the critical components which mediate an immune response preventive against severe malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Increased protection of mice was achieved by coadministration of dendritic cell-derived CC chemokine 1 with irradiated sporozoites (7). Earlier studies showed that IL-4-producing CD4 T cells in the liver were important for the development of a protective CD8 ϩ T-cell response against the malaria liver stage (8).…”
Section: Discussionmentioning
confidence: 99%